2009
DOI: 10.1097/yco.0b013e32832ed7ed
|View full text |Cite
|
Sign up to set email alerts
|

Pathological gambling and criminality

Abstract: While reviewing the present study, research work was published that contributed to a better understanding of the association between pathological gambling and criminality and went further into their complex relationship and the formulation of explanatory models related to impulsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 20 publications
2
25
0
3
Order By: Relevance
“…8,9 The results in this study suggest that this is not universal because 2% of the sample did not exhibit 5 or more criteria; however, all studies agree on the existence of a clear association between pathological gambling severity and the presence of illegal behavior. 15,16,34,35 Moreover, the data show that illegal acts provide the lowest contribution to the reliability of the pathological gambling diagnosis in patients seeking help for pathological gambling, and this is invariant to the patients' sex and age. Nonetheless, the presence of this behavior may be relevant from a clinical perspective as a way to assess the psychopathology related to the disorder and the severity of the gambling conduct.…”
Section: Discussionmentioning
confidence: 90%
“…8,9 The results in this study suggest that this is not universal because 2% of the sample did not exhibit 5 or more criteria; however, all studies agree on the existence of a clear association between pathological gambling severity and the presence of illegal behavior. 15,16,34,35 Moreover, the data show that illegal acts provide the lowest contribution to the reliability of the pathological gambling diagnosis in patients seeking help for pathological gambling, and this is invariant to the patients' sex and age. Nonetheless, the presence of this behavior may be relevant from a clinical perspective as a way to assess the psychopathology related to the disorder and the severity of the gambling conduct.…”
Section: Discussionmentioning
confidence: 90%
“…Regarding prostitution and gambling, the same basic argument can be made: People correctly perceive that both of these activities are positively associated with involvement in criminality (Brown, Killian, & Evans, 2005;Cohen & Felson, 1979;Ellis et al, 2009, p. 56;Folino & Abait, 2009;Johansson, Grant, Kim, Odlaug, & Götestam, 2009;Sampson, Raudenbush, & Earls, 1997). Because nearly everyone wants to suppress victimizing forms of criminality, large percentages of people favor legislation that limits access to prostitution and gambling activities.…”
Section: The Criminalization Of Victimless Offensesmentioning
confidence: 82%
“…The above-mentioned psychopathological symptoms of problem gambling were combined in Endel's case. Studies confirm that pathological gambling is associated with violence in couples (Afifi, Brownridge, MacMillan, & Sareen, 2010;Folino & Abait, 2009;Pulay et al, 2008). Interviews with spouses of gamblers indicate that intimate partner violence is more common among gamblers than in the general population, and samples of problem gamblers have shown significantly higher rates of perpetration of severe physical assault than previous studies have reported (Korman et al, 2008).…”
Section: The Journal Of Forensic Psychiatry and Psychology 161mentioning
confidence: 82%